FACTORS THAT INFLUENCE BEHAVIORAL INTENTION TO USE ACCURATE APPLICATIONS WITH THE UNIFIED THEORY OF ACCEPTANCE AND USE OF TECHNOLOGY MODEL IN STUDENTS OF THE FACULTY OF ECONOMICS, JAKARTA STATE UNIVERSITY - Muhamad Tahfidz; Tri Hesti Utaminingtyas; Ati Sumiati (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2024)
This research aims to determine the influence of performance expectancy, effort expectancy, and social influence on behavioral intention regarding the use of accuracy among students at the Faculty of Economics, Jakarta State University. Using quantitative research methods and the samples used were 115 samples. Taken using the purposive sampling method with the category of active students of Accounting Education, Jakarta State University, Class 2020-2022, and have used accurate in the last 1 (one) year. This research uses multiple regression analysis techniques with a hypothesis test consisting of the t test. The results obtained in this research are (1) There is an influence between performance expectancy and behavioral intention in Accounting Education students at Jakarta State University. (2) There is an influence between effort expectancy and behavioral intention in Accounting Education students at Jakarta State University. (3) There is an influence between social influence on behavioral intention in Accounting Education students at Jakarta State University. Based on this research, accurate can be an alternative in learning for financial and accounting data processing because it is easy to understand and helps in the accounting recording process supported by the availability of facilities and infrastructure for accurate learning.